Insect parasitoid and ant of associated on aphids (Aphididae) colonies on plants in West Java - Yani Maharani; Nina Maryana; Aunu Rauf; Purnama Hidayat (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2020)
Aphid is a sucking insect as a pest and vector of virus diseases plants. The aphids presence on plants are often accompanied by ants that symbiotic on aphid’s colony. Mutualism symbiosis between ants and aphids can hinder natural enemies especially parasitoids to parasitizing aphids. This study aims to explore parasitoid and ant species associated with aphids and determine the level of parasitoid parasitization. The survey was conducted on agricultural crops and weeds in West Java area. Samples were taken by purposive sampling looking at the aphid presence, ant, and mummified colonies. Aphid’s identification was carried out at Insect Biosystematics Laboratory, Department of Plant Protection IPB, whileparasitoid and ant identification was carried out at Entomology Laboratory of Zoology LIPI. The identification results obtained four species of Hymenoptera parasitoid, i.e Adialythus ambiguus, Aphidius matricariae, Praon absinthi (Braconidae) and Psyllaephagus pilossus (Encyrtidae) and eight species of ants of Formicidae family, i.e Dolichoderus sp, Dolichoderus thoracicus, Monomorium destructor, Monomorium floricola, Myrmicaria brunnea, Pheidole javana, Polyrhachis dives, and Technomyrmex albipes. The dominant parasitoid species found was A. matricariae, but the highest level of parasitization was P. pilossus (78%), parasites Rhopalosiphum padi in rice plants. Basic information on the types of ants and parasitoid insects associated with aphids can be used in the development of aphids integrated pest management strategies.